Dose-dependent esomeprasole antisecretory effect: results of long-term intragastric pH monitoring - S. A. Kurilovich; Ye. A. Chekalina; A. V. Belkovets; L. V. Scherbakova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study antisecretory activity of the first dose of esomeprazole (20 or 40 mg) (Emanera®, «KRKA», Slovenia) by long-term intragastric pH monitoring. Material and methods. Long-term intragastric pH monitoring was carried out in 20 patients with acidrelated diseases by «Gastroskan-24» device («IstokSistema», Fryazino, Russia). In the first 24 hours patients received no antisecretory agents, in the morning of the next day - they received esomeprazole 20 or 40 mg orally 30 min. prior to the breakfast. Median pH, both time with various pH values and area under pH distribution curve, percent of this time with values from 1,0 to 10,0 per day before and after esomeprazole administration were estimated. The respective scores were compared, using Wilcoxon criterion. Differences were considered to be significant at р